Understanding ring-closing and racemization to prepare α-amino acid NCA and NTA monomers: a DFT study. Issue 26 (25th June 2020) - Bai, Tianwen; Shen, Bo; Cai, Da; Luo, Yifan; Zhou, Peng; Xia, Jingya; Zheng, Botuo; Zhang, Ke; Xie, Rongze; Ni, Xufeng; Xu, Maosheng; Ling, Jun; et al.
Abstract : Our work demonstrates the detailed mechanism to synthesize NCA and NTA monomers and racemization process of optical pure monomers. Abstract : Polypeptides and polypeptoids are promising materials in biomedical applications bearing α-amino acid repeating units, which are prepared from ring-opening polymerizations of α-amino acid N -carboxyanhydride (NCA) or N -thiocarboxyanydride (NTA) monomers. Detailed studies on monomer synthetic routes are essential to explore new α-amino acid NCA and NTA monomers as well as the corresponding poly(α-amino acid) materials. In this contribution, density functional theory (DFT) is applied to investigate the mechanism of the Leuchs approach including two possible pathways, precursor structure and racemization in the ring-closing reaction. According to DFT calculations, pathway 2 is preferred with lower Δ G than pathway 1, and the rate-determining step is recognized as an SN 2 substitution with releasing equivalent halogenated hydrocarbon, which explains our experimental observations. Racemization results from the reaction between the NTA monomer and a strong protonic acid, which can be suppressed by low temperature and short reaction time. Racemization is inhibited by steric hindrance in those NTAs of α-amino acids containing high bulkiness at the β-carbon, such as leucine-NTA.